Search Engine Optimization All-in-One For Dummies - Clay, Bruce; Jones, Kristopher B. (For Dummies, 2022)
Get search engines to rank your site as the No. 1 result with help from this comprehensive resource What's the best hiding place in the world? The second page of Google's search results! If you want your website to be found, you need to make sure it appears prominently on search engines. In Search Engine Optimization All-in-One For Dummies, you'll find practical and easy-to-follow advice to increase your site's chances of landing that coveted No. 1 spot on Google, Bing, and other popular search engines. You'll discover how search engines decide which websites to rank highly, how to optimize your site for your best chance at the first page of organic results, what keywords to target, and even how to make your site internationally visible. You'll also find out how to: Optimize your webpage with responsive design that makes it irresistible to Google Create a keyword strategy that keeps interested and engaged visitors flowing to your website Generate the backlinks that will teach Google you're a trusted resource and help you climb the search engine results page Perfect for webmasters, bloggers, e-commerce professionals, and anyone else looking for more online visibility, Search Engine Optimization All-in-One For Dummies is a must-have guide to improving the quantity and quality of your web traffic.